The effects of weight training on pain relief and fatique in patients with fibromyalgia - Coetzer, Gerhardus (University of the Free State, 2014)
Objectives: The aim of this study was to determine the effect of weight training on pain relief and fatigue in patients with fibromyalgia (FM). Methods: This study was a randomized control study on patients diagnosed with FM. The group of FM patients was subjected to inclusion and exclusion criteria. Randomization was done on the patients who have met the inclusion criteria by the Department of Biostatistics at the University of The Free State. The experimental group was subjected to a training programme under supervision while the control group received verbal instructions to follow a training programme and the benefits thereof (Glombiewski et al., 2010), but did not undergo supervised training. The training period was 12 weeks. The subjects maintained their ordinary daily chores and physical activity. The experimental group started a supervised strength training period. Training was carried out 3 times a week and. During the first 3 weeks patients started with 8 - 12 repetitions for each set, with loads of 40 – 60% of the one repetition maximum (1 RM) and continued during the next 4 weeks with 10 – 12 repetitions with loads of 60 – 70% of 1 RM. Subsequently, during week 8 – 12 the number of repetitions was 10 for each set with loads of 60 – 80% of 1 RM. In addition to the muscle strengthening exercises each session ended with 5 – 10 minutes of core strengthening. All training sessions included warm up and cool down exercises using either a treadmill or bicycle ergometer and muscle stretching. Moreover, the subjects continued their ordinary chores and physical activities. The patients did a 15 minute warm up consisting of 10 minutes light aerobic work followed by 30 – 40 minutes weight training followed by 10 – 15 minutes of cool down. The programme differed from a Monday, to a Wednesday, to a Friday, where different muscle groups were targeted by the weight training. Results: The anthropometric characteristics in the current study for the exercise and control group are very similar. The Student T-Test was used to test for significant differences between the control and experimental group Fibromyalgia Impact Questionnaire (FIQ) scores over the 12 weeks. A 95% confidence interval was used to determine the difference between the two groups. The confidence interval shows that there is no statistical difference between the FM experimental (FMT) and FM control group (FMC). The following variable, V = FIQ: W4-W1 is where the FIQ score of week 4 were subtracted from week 1. No statistical difference (p<0.05) was observed between the control and the exersice group between week 1 and 4. The exercise group’s progress was statistically better (p<0.05) than control group in week 4 - 8. At week 8 the FMT group’s fibromyalgia impact questionnaire score median was 39 compared to the FMC group’s median of 63. Unfortunately, the exercise group deteriorated statistically significant (p<0.05) in the FIQ scores compared to control group improvement from week 8 – 12. Lastly, there was no statistical difference (p<0.05) between week 1 and week 12 between the FM control group and the exersise group regarding improvement of symptoms as reported in the FM impact questionnaire. Conclusions: It is still unclear what combination of type, intensity and duration of exercise treatment works best in the treatment of FM. It is important to recognize that in the case of a chronic pain disorder like FM, treatment must be focused not just on immediate symptom relief but also on maintaining long term lifestyle behaviour. As long as FM aetiology remains unclear, there is a need to explore mediating variables that can be used to intervene in order to ameliorate symptoms. Research efforts must continue to explore methods to relieve symptoms short term and support ongoing long term behaviour change to improve functioning and enhance the quality of life for patients with FM.
Dissertation (M.Sports.Med. (Sports Medicine))--University of the Free State, 2014
Keywords: Chronic diseases -- Exercise therapy; Exercise therapy; Pain -- Treatment; Fibromyalgia; Weight training